Checkpoint-Inhibition bei Tumorerkrankungen - Ben Khaled, Najib; Piseddu, Ignazio; Boehmer, Daniel F. R.; Zierold, Sarah; Heinzerling, Lucie; Mayerle, Julia; De Toni, Enrico N. (Onkologe, 2021)
Background: The introduction of immune checkpoint inhibitors (ICI) into the therapeutic landscape in oncology over the last decade represents a fundamental advancement in cancer immunotherapy. Objectives: We review the mechanism of action of ICI and their current use in the systemic therapy of various cancers. Materials and methods: Relevant articles were identified in the PubMed database. Clinical trial information was extracted from the Clinicaltrials.gov registry; information on drug approvals were obtained from the European Medicines Agency and the U.S. Food and Drug Administration databases. Conclusions: Although substantial improvements in the treatment of many types of cancer have been achieved by ICI, durable responses and long-term survival can only be observed in a small number of patients. The development of predictive biomarkers to maximize efficacy and minimize immune-related toxicity, in addition to new combination regimens, may help unleash the full potential of ICI in cancer immunotherapy.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Biomarkers; Cancer treatment; CTLA-4-Inhibitor; Immunotherapy; PD-1-PD-L1 blockade